Integrasi Kearifan Lokal dalam Kebijakan Daerah: Studi Kualitatif Tentang Penguatan Pengobatan Herbal di Kota Surakarta - Sugianto Kurniadi; Yuliarti Yuliarti; Yuli Susilowati; Wirda Rohmah (Badan Riset dan Inovasi Daerah Kota Surakarta, 2026)
This study aims to examine the integration of local wisdom into regional policies, particularly concerning the strengthening of herbal medicine in Surakarta City. As a city with a strong Javanese cultural heritage, Surakarta holds significant potential in developing traditional herbal medicine rooted in local values and empirical community practices. The research method employed is library research, involving an in-depth review of academic literature, regional regulations, and relevant policy documents. The analysis was conducted qualitatively using a descriptive-analytical approach to identify patterns of integration between local wisdom, traditional health systems, and regional government policies. The findings indicate that the success of strengthening herbal medicine is strongly influenced by the synergy between the preservation of local knowledge, regulatory support, and partnerships among traditional practitioners, academics, and government institutions. Moreover, the integration of local wisdom into regional policy not only contributes to local economic development but also enhances community health independence. This study emphasizes the importance of culturally grounded yet innovative policies in addressing the health needs of modern society.